EFEKTIVITAS JUS TOMAT DAN JUS NANAS TERHADAP PERUBAHAN TEKANAN DARAH PENDERITA HIPERTENSI DI SLEMAN - Handari, Murgi; Sihotang, Feberianti; Ambarwati, Eny Retna (MEDIA ILMU KESEHATAN, 2020)
Background: hypertensive is the major health problem in indonesia. the highest prevalence of hypertension in indonesia is in the 35-44 years age group (31,6%). treatment of hypertension can use non-pharmacological therapies including tomatoes juice and pineapples juice therapy.Objective: the difference of giving tomatoes juice and pineapples juice on reducing blood pressure in patients with hypertension in sleman.Methods: this research was a quantitative study, used a quasi-experimental method with pre and post test one group design. the sample amount was 30 peoples who were divided into two groups, each group consist of 15 peoples. the sampling technique used purposive sampling. data analysis used paired t test and independent t test. Results: the paired t test results in the systolic and diastolic groups of tomatoes juice values p=0,000 and 0.001, while the systolic and diastolic pineapples juice groups had a similarity of values p=0,000, in both groups have value p<0.05. the results of independent t test on average systolic and diastolic blood pressure after given tomatoes juice therapy were 139.33 / 87.33 mmhg with value p=0.007 and pineapples juice therapy 127.33 / 76 mmhg with value p=0.001.Conclusion: there was a difference in effect between of tomatoes juice and pineapples juice on blood pressure in people with hypertension.